Autoimmune Conditions in 235 Hemochromatosis Probands with HFE C282Y Homozygosity and Their First-Degree Relatives - James C. Barton; J. Clayborn Barton (Journal of Immunology Research)
We performed a retrospective study of autoimmune conditions (ACs) in 235 hemochromatosis probands at diagnosis by analyzing age, sex, ACs, history of first-degree family members with ACs (FH), diabetes, heavy ethanol consumption, elevated serum ALT/AST, nonalcoholic fatty liver disease, viral hepatitis, cirrhosis, iron removed to achieve iron depletion (QFe), and positivity for human leukocyte antigen (HLA) haplotypes A∗01, B∗08; A∗02, B∗44; A∗03, B∗07; A∗03, B∗14; and A∗29, B∗44. There were 138 men (58.7%). Median followup was 19.6 y. One or more of 19 ACs were diagnosed in each of 35 probands (14.9%). Prevalences of Hashimoto’s thyroiditis, rheumatoid arthritis, and ankylosing spondylitis were 8.1% (95% CI: [5.1, 12.5]), 1.7% [0.6, 4.6], and 0.0085 [0.0015, 0.0337], respectively. Eighteen probands (7.7%) had a FH. Eight probands with ACs had 9 family members with ACs. In a logistic regression, ACs were less likely in men (odds ratio (OR) 0.3 [0.1, 0.6]) and more likely in probands with a FH (OR 4.1 [1.4, 11.8]). Overall ACs risk was not significantly associated with QFe or HLA haplotypes. Estimated survival of probands with and without ACs did not differ significantly. We conclude that ACs are common in hemochromatosis probands, especially women and probands with a FH.